Medical students’ perception on their educational environment by using Dundee Ready Educational Environment Measure at a Malaysian medical school - Mohd Tambeh, Siti Norashikin; Yaman, Mohamad Nurman; Zahedi, Farah Dayana; Abdul Nasir, Nurul Alimah (Bangladesh Journal of Medical Science, 2024)
Background Optimal educational environment in medical school has been shown to have desirable effects on medical students. In providing this environment, the input from medical students is proven to be a necessity. Objectives: The objective of this study is to obtain the perception of preclinical and clinical students on their current educational environment. Methods A cross-sectional study using self-administered Dundee Ready Education Environment Measure (DREEM) questionnaire was conducted among medical students in UiTM to measure their perception on educational environment. DREEM consisted of 50 items grouped into five subscales which addressed different aspects of educational environment: students’ perception of learning (SPoL), teachers (SPoT), atmosphere (SPoA), academic self-perception (SASP) and social self-perception (SSSP). Results A total of 894 out of 1165 students completed the questionnaire. The overall mean score of DREEM was described as more positive than negative (mean score: 131.81/200), with significant difference between pre-clinical and clinical students in SPoL and SSSP subscales. SPoL was interpreted as having a more positive perception (mean score: 33.06/48), SPoT as moving in the right direction (mean score: 30.11/44), SASP as feeling more on the positive side (mean score: 20.75/32), SPoA as having a more positive attitude (mean score: 30.72/58, and SSSP as not too bad (mean score: 17.17/28). Educators were perceived as being knowledgeable, encouraging students to participate, and wellprepared for class. Students also perceived that they have good friends, learnt a lot on empathy and the knowledge taught was relevant for future career. All students perceived that educators were authoritarian, overemphasized on factual learning, and they were unable to memorise all. Clinical students viewed educators to be angry in class, too tired to enjoy the course, stressful and lonely. Conclusion In conclusion, the educational environment was viewed positively by the students with clinical students having more areas of concern when compared to pre-clinical students. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1168-1177